The Management of Classroom Routines in Iraqi EFL University Teaching from Instructors' View Point - Gumar Karam, Hussein (Journal of College of Education, 2022)
Abstract    Routines are the basis of classroom management and the key to learning. Classroom routines provide the environment for learning. Valuable classroom management helps instructors keep students’ learning on the go. Classroom routines can certainly influence students’ academic performance. This study uncovers the sort of classroom management routines Iraqi EFL Instructors use. The study sample included 31 EFL instructors from the College of Education for Humanities, Wasit University. Results suggested that item (30) achieved the highest weighted mean (4.71. 94%), whilst item (27) achieved the lowest weighted mean (2.49. 48%). The study, therefore, recommends that Iraqi EFL instructors are urged to follow more effective classroom management techniques to support classroom learning.
Keywords: Key Words: Routines, Classroom Management, Teaching, Learning, and Iraq EFL Universities undergraduates